Tree-based Multicast Key Management in ubiquitous computing environment. (29th July 2011) - Yao, Lin; Kong, Xiangwei; Wu, Guowei; Lin, Chi; Fan, Qingna
A Tree-based Multicast group Key Management (TMKM) protocol for ubiquitous computing is proposed to generate, distribute, and update the group key. The whole group is divided into the server layer and the user layer, and the user layer is further divided into subgroups. Every subgroup is initialised as a balanced binary tree. We employ hierarchical group key management method for the whole topology and centralised group key management method for subgroup, so TMKM takes advantage of centralised and distributed key group management. Compared with some other group key management protocols, TMKM shows higher superiority on security, scalability and computation complexity.